The effect of health literacy on vaccine hesitancy among Italian anticoagulated population during COVID-19 pandemic: the moderating role of health engagement - Arianna Magon; Cristina Arrigoni; Guendalina Graffigna; Serena Barello; Marco Moia; Gualtiero Palareti; Rosario Caruso (Taylor & Francis Group, 2021)
Assessing vaccine hesitancy and its determinants is pivotal to optimize vaccine acceptance in anticoagulated patients, given that this population has been described to have a higher risk of severe COVID-19-related complications. This study assessed the moderator role of patients' health engagement on the relationship between health literacy and vaccine hesitancy. A web-based survey was performed in Italy during the first wave (June-August 2020) and the second wave (October 2020-March 2021) of the COVID-19 pandemic, enrolling 288 patients. The rates of vaccine hesitancy reported during the first pandemic wave were 38.4% and 30.8% during the second wave (when a vaccine was available) (p = .164). A moderation analysis was performed to assess the role of health engagement in influencing the relationship from health literacy to vaccine hesitancy. Patients' health engagement enhanced the effects of health literacy on decreasing vaccine hesitancy (p < .001), suggesting that co-construction strategies for communicative action are pivotal.